2000
DOI: 10.1034/j.1399-6576.2000.440803.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of post‐herpetic neuralgia: acyclovir and prednisolone versus epidural local anesthetic and methylprednisolone

Abstract: Epidural administration of local anesthetic and methylprednisolone is significantly more effective in preventing PHN at 12 months compared to intravenous acyclovir and prednisolone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
2
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(126 citation statements)
references
References 45 publications
2
117
2
4
Order By: Relevance
“…A review of neuraxial (including sympathetic) blockade for the treatment of HZ-associated pain found that 71% (12/15) of studies (Kumar, Krone et al, 2004), only one of which was an RCT (Pasqualucci et al, 2000 Level II), reported a reduction in either the incidence or severity of HZ-associated pain to 1 month. In a subsequent RCT, there was a significant difference in the incidence (and to a lesser extent the intensity) of HZ pain in patients who received a single epidural methylprednisolone and bupivacaine injection, compared with those who received antiviral therapy and analgesia as 'standard care'; the NNT for complete resolution of HZ pain at 1 month with the epidural injection was 10 (van Wijck et al, 2006 Level II).…”
Section: Neuraxial or Sympathetic Blockadementioning
confidence: 99%
“…A review of neuraxial (including sympathetic) blockade for the treatment of HZ-associated pain found that 71% (12/15) of studies (Kumar, Krone et al, 2004), only one of which was an RCT (Pasqualucci et al, 2000 Level II), reported a reduction in either the incidence or severity of HZ-associated pain to 1 month. In a subsequent RCT, there was a significant difference in the incidence (and to a lesser extent the intensity) of HZ pain in patients who received a single epidural methylprednisolone and bupivacaine injection, compared with those who received antiviral therapy and analgesia as 'standard care'; the NNT for complete resolution of HZ pain at 1 month with the epidural injection was 10 (van Wijck et al, 2006 Level II).…”
Section: Neuraxial or Sympathetic Blockadementioning
confidence: 99%
“…При отсутствия инфекционной причины реко-мендовано применение кортикостероидов в виде локаль-ных инъекций и системно. Есть данные о том, что их ран-нее применение уменьшает риск хронизации болевого синдрома [6,[33][34][35][36]. Одной из специфических причин развития невропатии является герпетическое поражение, которое может вызвать постгерпетическую невралгию.…”
Section: постоянная невропатическая больunclassified
“…Однако нет до-казательств, что именно локальное введение витаминов группы В позволяет уменьшить зуд и болевой синдром, так как группы сравнения, получавшей витамины В 1 и В 12 системно, в этом исследовании не было. Свидетельства об эффективности паравертебральных [35] и эпидуральных [38,36] блокад с анестетиками и глюкокортикоидами для предотвращения развития постгерпетической невралгии протворечивы. В двух исследованиях [35,36] было показа-но преимущество локального введения 10 мг бупивокаина и 80 мг метилпреднизолона перед стандартной противо-вирусной терапией и системным введением глюкокорти-коидов, в одном [38] не показано, к тому же пока не ясно, можно ли экстраполировать результаты этих исследова-ний на ЛБ.…”
Section: постоянная невропатическая больunclassified
“…Yanagida et al reported no prophylactic effect of early sympathetic blockade on PHN (Yanagida et al, 1987). Two randomized trials have been performed for the prevention of PHN by single or repetitive epidural injections of anesthetics and steroids in the acute HZ (van Wijck et al, 2006;Pasqualucci et al, 2000). Van Wijck et al showed no significant effect of epidural injections in reducing the incidence of PHN; Pasqualucci et al reported that repetitive epidural administration of bupivacaine and methylprednisolone was significantly more effective in preventing PHN at 12 months compared with acyclovir and prednisolone.…”
Section: Nerve Blocksmentioning
confidence: 99%